Analysis of Arabic Language Textbooks (Naḥwu and Ṣaraf) for Grade X Islamic Senior High Schools with Religious Interests Published by the Ministry of Religion (A Study of Book Content Analysis Based on Mackey's Theory) - Helga Regita Safira; Siti Mumun Muniroh (International Research and Development for Human Beings (IRDH), 2024)
This research is motivated by the problems found in the Arabic textbooks of madrasahs, such as language errors and not being by BSNP standards. This study aims to determine the quality of the Arabic textbooks (naḥwu and ṣaraf) of Madrasah Aliyah religious interests for class X. This research is included in literature or library research, while the researcher uses content analysis to analyze the data.The results of this study indicate that this book is suitable for learning for class X students. Based on this research, it can be concluded in general that the quality of the material in this textbook has met the principles of material selection, gradation, presentation, and repetition. However, from the presentation principle, it only uses one of the four aspects of the presentation process such as differential, ostensive, pictorial, and context procedures. The advantages of this book from the aspect of selection based on availability include the vocabulary ظرَ ةَحلْ ,رِسافَ ,بَ هَ َذ , َن رِ whose use in this textbook is by the context or situation, the gradation aspect based on the rules of naḥwu and ṣaraf uses a straight gradation pattern and based on linguistic categories uses a grammatical gradation pattern, the presentation aspect based on the pictorial procedure of this textbook presents schematic images in the discussion of the rules of naḥwu and ṣaraf, and the repetition aspect based on the sharpening technique uses receptive and productive repetition and presents varied exercises. The shortcomings of this book in terms of selection based on the vocabulary range ب حَ يْلِ are not often used in Indonesia, in terms of gradation, there are titles of naḥwu and ṣaraf rules that are presented that do not match the curriculum title, in terms of presentation, there are no ostensive procedures and several chapters do not present context and pictorial procedures, and in terms of repetition, there is a repetition of writing practice questions on page 78.